Legal Protection for Victims of Narcotic Abuse in Baitu Syifa Rehabilitation Institution, Medan Through a Worship Approach - Hari Suyandi R; Zulkarnain Zulkarnain; Ramadhan Syahmedi Siregar (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The existence of a rehabilitation centre for addicts and victims of narcotics abuse is considered an effective formula to protect the law. In contrast, currently, prisons are considered inappropriate and safe for narcotics addicts to undergo healing. This study examines the worship approach used in the rehabilitation process and the application of legal protection for someone involved in narcotics abuse at the Baitu Syifa Rehabilitation Center from the perspective of the Narcotics Law Number 35 of 2009. This qualitative research uses statutory, case and conceptual approaches. The study results found that the rehabilitation program at Baitu Syifa did not conflict with the provisions in Article 57 of the Law. Number 35 of 2009 states that residents' recovery can be carried out through a religious approach. The recovery of victims of narcotics abuse in Baitu Syifa is in the form of routine activities with Islamic nuances based on the Al-Quran and As-sunnah, which include Islamic Treatment Community (TC), Scientific Islamic Studies, pious practices such as performing obligatory prayers, sunnah services, the Nabawi treating and reading the Koran. The development of worship approach methods at the Baitu Syifa Rehabilitation Center has been adapted to Islamic law